Push and pull factors of youth involvement in outdoor recreation activities - Juhari, Nur Syahida (2019)
Youth involvement in outdoor recreation activities is still very low because youth these days are more interested in social networking and fun activities. Hence, it is important to understand the needs and wants of youth to attract more youth to be involved in outdoor recreation activities. The objective of this study is to determine the push and pull factors of youth involvement in outdoor recreation activities among local undergraduate students in Universiti Putra Malaysia. The study also compares the push and pull factors between the faculties. Self-reported questionnaire was distributed to 198 students from six faculties. Results shows that the most important push and pull factors of youth involvement are Self Actualization (M= 4.254, SD=0.473) and Infrastructure (M=4.411, SD=0.410). Besides, one of the push factors that show significant differences between faculties is the Social Need factor. Based on Post-Hoc test, significant differences were observed between Faculty of Forestry (M=3.826, SD=0.403) with Faculty of Veterinary Medicine (M=4.102, SD=0.282), Faculty of Medicine and Health Science (M=4.091, SD=0.476) and Faculty of Environmental Science (M=4.258, SD=0.265). However, no significant differences were observed between faculties for all pull factors.